Gamification for teacher professional development: the case for narrative approaches - Francesca Pozzi; Donatella Persico (Interaction Design and Architecture(s))
Although gamification and the use of serious games in education are usually recommended, according to the literature in the field it seems these approaches are hardly used in teacher training contexts. This might depend on the fact that the use of strategies such as Points, Leaderboards and Badges, do not fit well with a context where collaboration and practice sharing need to be encouraged, rather than hindered by competitive mechanics. In this sense, narrative approaches seem to fit better with these contexts. In this paper we propose a gamification approach for Teacher Professional Development based on a narrative approach. Thanks to an exploratory study, we have tested the proposed approach and collected preliminary data that are presented. The main results are encouraging, as teachers’ reactions were positive in respect to the usefulness and effectiveness of the proposed approach and also in respect to their willingness to apply similar gamification strategies in their practice.